2006
DOI: 10.1158/0008-5472.can-05-3090
|View full text |Cite
|
Sign up to set email alerts
|

EGFR Tyrosine Kinase Inhibitors Decrease VEGF Expression by Both Hypoxia-Inducible Factor (HIF)-1–Independent and HIF-1–Dependent Mechanisms

Abstract: Epidermal growth factor receptor (EGFR) inhibitors can decrease vascular endothelial growth factor (VEGF) expression and tumor angiogenesis. In the current study, we investigate the molecular pathways by which this occurs using two drugs that have been used in the clinic, gefitinib (Iressa) and erlotinib (Tarceva). The decrease in VEGF expression by gefitinib in SQ20B squamous cell carcinoma cells was opposed by adenoviral expression of Akt in these cells. The hypoxia-inducible factor-1 (HIF-1) binding site lo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
179
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(195 citation statements)
references
References 35 publications
(42 reference statements)
13
179
1
2
Order By: Relevance
“…However, little was known about the mechanism of FSH stimulation on VEGF expression. Other studies showed HIF-1α and survivin may play a role in VEGF expression [7][8][9][10][13][14][15][16], and it had also been shown that FSH induces HIF-1α and survivin expression [37][38][39]. In this study, we showed that treatment with FSH also increased survivin and HIF-1α expression (Figure 2A and 2B).…”
Section: Discussionsupporting
confidence: 74%
“…However, little was known about the mechanism of FSH stimulation on VEGF expression. Other studies showed HIF-1α and survivin may play a role in VEGF expression [7][8][9][10][13][14][15][16], and it had also been shown that FSH induces HIF-1α and survivin expression [37][38][39]. In this study, we showed that treatment with FSH also increased survivin and HIF-1α expression (Figure 2A and 2B).…”
Section: Discussionsupporting
confidence: 74%
“…Lee et al 2000;Winkler et al 2004;Dings et al 2007;Fischer et al 2007;Eichhorn et al 2008;Batra et al 2009;Skuli et al 2009;McGee et al 2010. j Teicher et al 1995bJain et al 1998;Bernsen et al 1999;Cohen-Jonathan et al 2001;Delmas et al 2003;Ansiaux et al 2005Ansiaux et al , 2006Pore et al 2006b;Segers et al 2006;Cerniglia et al 2009;Qayum et al 2009;Cham et al 2010. k Ader et al 2003;Hamzah et al 2008;Kashiwagi et al 2008;Stockmann et al 2008;Maione et al 2009;Mazzone et al 2009;Skuli et al 2009;Tsukada et al 2009;Rolny et al 2011. l Yuan et al 1996Lee et al 2000;Wildiers et al 2003;Tong et al 2004;Nakahara et al 2006;Dickson et al 2007b;Kurozumi et al 2007;Taguchi et al 2008;Zhou et al 2008;Kamoun et al 2009;Ohta et al 2009;Gallo 2009. m Jain et al 1998;Izumi et al 2002;…”
Section: Vegfunclassified
“…In fact, overwhelming evidence indicates that HIF-a is indeed overexpressed in the majority of human cancers (17)(18)(19), where it is associated with patient mortality and poor response to treatment (20)(21)(22)(23)(24), findings that can be hardly reconciled with a negative role of HIF-1 in tumor growth. Importantly, the association of several oncogenic and receptor tyrosine kinase -dependent signaling pathways, frequently deregulated in human cancers, with HIF-1a activation also suggests that many of these pathways converge on or implicate HIF-1 in mediating cell survival and growth (25)(26)(27)(28). However, staining of HIF-1a in human cancers is variable, from few positive cells up to the majority of tumor tissue, and characterized by distinct patterns of expression, of which the implications and biological consequences are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%